Suitability of potyviral recombinant virus-like particles bearing a complete food allergen for immunotherapy vaccines - Pazos-Castro, Diego; Margain, Clémence; Gonzalez-Klein, Zulema; Amores-Borge, Marina; Yuste-Calvo, Carmen; Garrido-Arandia, Maria; Zurita, Lucía; Esteban, Vanesa; Tome-Amat, Jaime; Diaz-Perales, Araceli; Ponz, Fernando (Frontiers in Immunology, 2022)
Virus-like particles (VLPs) have been gaining attention as potential platforms for delivery of cargos in nanomedicine. Although animal viruses are largely selected due to their immunostimulatory capacities, VLPs from plant viruses constitute a promising alternative to be considered. VLPs derived from Turnip mosaic virus (TuMV) have proven to present a tridimensional structure suited to display molecules of interest on their surface, making them interesting tools to be studied in theragnostic strategies. Here, we study their potential in the treatment of food allergy by genetically coupling TuMV-derived VLPs to Pru p 3, one of the most dominant allergens in Mediterranean climates. VLPs-Pru p 3 were generated by cloning a synthetic gene encoding the TuMV coat protein and Pru p 3, separated by a linker, into a transient high-expression vector, followed by agroinfiltration in Nicotiana benthamiana plants. The generated fusion protein self-assembled in planta to form the VLPs, which were purified by exclusion chromatography. Their elongated morphology was confirmed by electron microscopy and their size ( 400 nm), and monodispersity was confirmed by dynamic light scattering. Initial in vitro characterization confirmed that they were able to induce proliferation of human immune cells. This proliferative capability was enhanced when coupled with the natural lipid ligand of Pru p 3. The resultant formulation, called VLP-Complex, was also able to be transported by intestinal epithelial cells, without affecting the monolayer integrity. In light of all these results, VLP-Complex was furtherly tested in a mouse model of food allergy. Sublingual administration of VLP-Complex could effectively reduce some serological markers associated with allergic responses in mice, such as anti-Pru p 3 sIgE and sIgG2a. Noteworthy, no associated macroscopic, nephritic, or hepatic toxicity was detected, as assessed by weight, blood urea nitrogen (BUN) and galectin-3 analyses, respectively. Our results highlight the standardized production of allergen-coated TuMV-VLPs in N. benthamiana plants. The resulting formula exerts notable immunomodulatory properties without the need for potentially hazardous adjuvants. Accordingly, no detectable toxicity associated to their administration was detected. As a result, we propose them as good candidates to be furtherly studied in the treatment of immune-based pathologies.